2022
DOI: 10.3390/polym14112206
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Glutamic Acid or Amino-Protected Glutamic Acid into Poly(Glycerol Sebacate): Synthesis and Characterization

Abstract: Poly(glycerol sebacate) (PGS), a soft, tough elastomer with excellent biocompatibility, has been exploited successfully in many tissue engineering applications. Although tunable to some extent, the rapid in vivo degradation kinetics of PGS is not compatible with the healing rate of some tissues. The incorporation of L-glutamic acid into a PGS network with an aim to retard the degradation rate of PGS through the formation of peptide bonds was conducted in this study. A series of poly(glycerol sebacate glutamate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Jiang et al conducted a synthesis of various poly(glyceryl sebacate glutamate) (PGSE) elastomers, each characterized by a distinct proportioning of sebacic acid and l -glutamic acid. 43 They performed experimental assessments of mechanical properties and enzymatic degradation. The research demonstrated that the introduction of peptide linkages, courtesy of l -glutamic acid, significantly modified the mechanical properties and decelerated the degradation process in PGSE.…”
Section: Degradation Mechanism Of Dbementioning
confidence: 99%
“…Jiang et al conducted a synthesis of various poly(glyceryl sebacate glutamate) (PGSE) elastomers, each characterized by a distinct proportioning of sebacic acid and l -glutamic acid. 43 They performed experimental assessments of mechanical properties and enzymatic degradation. The research demonstrated that the introduction of peptide linkages, courtesy of l -glutamic acid, significantly modified the mechanical properties and decelerated the degradation process in PGSE.…”
Section: Degradation Mechanism Of Dbementioning
confidence: 99%